Effectiveness of industrialised building system (IBS) implementation for Malaysian Construction Industry - Zawawi, Mardhiah (2009)
Generally, the used of Industrialised Building System (IBS) in construction industry throughout the world has positive perceptions on improving the overall construction industry performance. Therefore, Construction Industry Development Board (CIDB) has been actively promoting the use of Industrialised Building System (IBS) in Malaysian Construction Industry since 1998. Unfortunately, the used of IBS for building project in Malaysia is still limited if compared to CIDB's target. In view to this limitation, this study has been carried out to evaluate the effectiveness of current IBS implementation for Malaysian construction industry through the measurement of acceptance level on the current IBS implementation and also determination of the existing problems faced by construction industry related to the IBS implementation. The methodologies adopted for this study are interview with expert panels and questionnaire survey. The result of this study revealed that current promotion on IBS for awareness purposes is effective but unfortunately the application is still very limited since it only covers certain elements. Not all practitioners can accept it implementation especially company and personnel with less experiences in handling IBS project. It is recommended that the relevant institution which produce young engineer for construction sector must provide a syllabus on IBS which cover technical, business process, and all aspect which needed for effective IBS implementation. This can generates wider range of application of IBS product within the industry